Squamous cell carcinoma of the urinary bladder: Systematic review of clinical characteristics and therapeutic approaches - Jeremy Martin; Estrella M. Carballido; Ahmed Ahmed; Bilal Farhan; Rahul Dutta; Cody Smith; Ramy F. Youssef (2016)
To highlight the current understanding of the epidemiology, clinicopathological characteristics, and management of squamous cell carcinoma (SCC) of the bladder, as it accounts for 2-5% of bladder tumours, with a focus on non-bilharzial-associated SCC (NB-SCC). The standard treatment for bladder SCC remains radical cystectomy (RC). We present an updated clinical profile of bladder SCC and a review of NB-SCC therapeutic approaches, including RC, neoadjuvant and adjuvant treatments, radiotherapy, chemotherapy, and immunotherapy.Using search terms relating to SCC, urinary bladder, and treatment modalities, we performed a search of the PubMed and Embase databases to identify NB-SCC treatment approaches and outcomes. Peer-reviewed English language reports from 1975 to present assessing SCC management were included. Two authors independently screened and extracted the data.Of the 806 articles screened, 10 met the pre-defined inclusion criteria. RC was performed in seven of the 10 studies. Although radiotherapy alone yielded poor outcomes, preoperative radiotherapy and RC were associated with improved survival. There is little evidence supporting the use of chemotherapy in NB-SCC, and its efficacy in relation to RC is not known.Based on current literature, there is insufficient evidence to provide a treatment recommendation for NB-SCC. Whilst RC is the standard of care, the role of preoperative radiotherapy should be revisited and compared to RC alone. Additional studies incorporating multimodal approaches, contemporary radiation techniques, and systemic therapies are warranted. Immunotherapy as a treatment for bladder SCC has yet to be investigated.